Magic and Magicians in the Middle Ages and the Early Modern Time: The Occult in Pre-Modern Sciences, Medicine, Literature, Religion, and Astrology - Classen, Albrecht (Fundamentals of Medieval and Early Modern Culture, 2017)
"Table of Contents" -- "List of Illustrations" -- "Magic in the Middle Ages and the Early Modern Age â Literature, Science, Religion, Philosophy, Music, and Art. An Introduction" -- "Magical (and Maligned) Metalworkers: Understanding Representations of Early and High Medieval Blacksmiths" -- "Painted Eyes, Magical Sieves and Carved Runes: Charms for Catching and Punishing Thieves in the Medieval and Early Modern Germanic Tradition" -- "Constructing the Magical Biography of the Irish Druid Mog Ruith" -- "Zum Umgang mit Zauberern im Rahmen frÃ¼hmittelalterlicher Missionsanstrengungen (Dealing with Magicians Within the Framework of Early Medieval Missionizing Efforts)" -- "Magic and Science: The Portail des libraires, Rouen" -- "The Magic of Love: Queen Isolde, the Magician Clinschor, and âSeeingâ in Gottfriedâs Tristan and Wolframâs Parzival" -- "Magical Gifts in Gottfried von Strassburgâs Tristan und Isolde and the Rejection of Magic" -- "Was Eustace Diabolical? Magic and Devilry in Le roman de Wistasse le moine" -- "Merlin, or, a Prophet Turning Magician" -- "The Book of Zabulon â A Quest for Hidden Secrets: Intertextuality and Magical Genealogy in Middle High German Literature, with an Emphasis on Reinfried von Braunschweig" -- "Miracles and Magic: Necromantic Practices Found in Cantiga 125" -- "Magic at the Margins: The Mystification of Maugis dâAigremont" -- "The Magician at Home with his Family: Comparative Historical Ethnographies of Two Pre- Modern Magicians from Autobiographical Sources: John of Morigny and the Tibetan Monk Milarepa" -- "Curious Clerks: Image Magic and Chaucerian Poetics" -- "Representing Magic and Science in The Franklinâs Tale and The Canonâs Yeomanâs Tale: Chaucerâs Exploration of Connected Topics" -- "Magic in Late Medieval German Literature: The Case of the Good Magician Malagis